The Correlation Between Changes in Interincisal Angles and Facial Profile Following Anterior Teeth Retraction in Orthodontic Treatment - Utari, Tita Ratya; Wardana, Puspitarini Nindya; Abdurrohman, Muhamat Muhtar S.; Risqi, Ashfi Amalina (Universitas Muhammadiyah Yogyakarta, 2025)
An essential aspect of orthodontic treatment planning is assessing the alignment of the upper and lower incisors, which can be determined by measuring the interincisal angle. Retracting the anterior teeth results in a change in the angle of the upper and lower incisors, which is anticipated to enhance the facial profile. This study aims to determine changes in interincisal angle and their relationship with changes in facial profile in patients with fixed orthodontic treatment with premolars extraction and have had anterior teeth retracted. The study used 25 cephalometric X-ray samples before treatment and after anterior tooth retraction from fixed orthodontic patients at RSGM UMY. The interincisal angle was measured utilizing the WebCeph application, and the soft tissue profile angle was assessed using ImageJ software, where the landmark points employed in the lateral photo using the Graber method. The data were then analyzed using SPSS with a paired t-test and Spearman. The results exhibited a significant difference in the interincisal angle (sig. value 0.000 <0.05), but no significant difference in the facial profile angle (sig. value 0.072 > 0.05). The Spearman test indicating no significant relationship between changes in interincisal and profile angle (sig. 0.189, p>0.05). In this case, retraction induces a change in the inclination of the anterior teeth but does not lead to a substantial change in the profile angle. Various elements, including the morphology, thickness, and tonicity of the soft tissue, as well as the patient's muscle pattern, might affect changes in the soft tissue profile.